Erich Fromm and global public sociology - McLaughlin, Neil (Public sociology series., 2021)
As the rise of global right-wing populism and Trumpism creates new interest in psycho-social writing and popular sociology, this timely book tells the story of the rise, fall and contemporary revival of the thoeries of Erich Fromm, a 1930s influential and creative public intellectual.